A Literary Study On Clinical Management On Pandu Vyadhi: A Brief Review - Khichariya, S D; Baghel, Pramod Kumar; Chandeshwar, Sonal (International Research Journal of Ayurveda & Yoga, 2021)
Pandu Roga (Anemia) is an illness characterized by a lack of hemoglobin and Dhatus, which is caused by a lack of iron in the diet. Skin discoloration to Shweta (whitish), Pita (yellowish), and Harita (greenish), as well as the presence of Ketaki Dhuli Nibha Chaya (discoloration resembling the color of the Pandanus flowers) are symptoms of these diseases. Palpitations, loss of appetite, Pandutwa (paleness), and skin dryness are some of the symptoms. Pandu Roga (Anaemia) as Anaemia is how contemporary science resembles Pandu Roga (Anaemia). For the treatment of Pandu Roga (Anaemia), the Ayurvedic system proposed a variety of therapeutic methods. This Scientific Paper summarizes Pandu Roga (Anaemia)’s Ayurvedic viewpoint.